Too Good To Be True: Influencing Credibility Perceptions with Signaling Reference Explicitness and Assurance Depth - Carolin Baier; Max Göttsche; Andreas Hellmann; Frank Schiemann (Journal of Business Ethics, 2021)
We investigate how the selection of assurance topics and the format of their communication influence the credibility perception of sustainability report readers. This is important because misleading communication may discredit ethical sustainability assurance practices. Based on signaling theory and using an experimental approach, we are the first to examine false credibility signals in the context of sustainability assurance. We find that two variables related to sustainability assurance, reference explicitness and assurance depth, jointly influence the assurance signal and the perceived credibility of a sustainability report. Our findings indicate that readers are not at risk of false signaling but can make incorrect interpretations of the assurance signal and might respond negatively to well-intentioned signals. The main implications of our findings are that firms should refrain from increasing reference explicitness and should select only the most material topics. Taken together, our results provide new insights on the unethical practice of false signaling and provide an example of an incorrect signal interpretation by readers.
Keywords: 300; Sustainability assurance; Perceived credibility; False signaling